Study on Seasonal Variation in Stroke (Medicine Today, 2022)
Introduction: After coronary artery disease and cancer, stroke is the third commonest cause of death in the developed countries. There have been descriptions of a seasonal variation in the frequency of different types of stroke. This variation may be related to a variation in the frequency of risk factors of stroke.Objective: To find out the seasonal variation of different type of strokes.Materials & methods: This cross sectional observational study was carried out at the department of medicine, mymensingh medical college hospital, mymensingh over a period of one year between June 2011 to May 2012. A total 292 patients of CT scan proven acute stroke of both sexes who were hospitalized within one weeks of acute stroke were included in this study within this period. data were processed and analyzed by computer software SPSS. Level of significance was considered as p value less than 0.05.Results: The frequency of ischaemic stroke during summer (62.4%) was significantly greater than that during winter (37.8%). The frequency of haemorrhagic stroke during winter (62.2%) was significantly greater than that during summer (37.6%). Hypertension was the most important risk factor and other risk factors were smoking, diabetes mellitus, tobacco chewing, ischemic heart disease, dyslipidemia, oral contraceptive pill, alcohol consumption, atrial fibrillation and past history of stroke.Conclusion: This study found stroke is influenced by the variation of seasons. The frequency of ischaemic stroke during summer was significantly greater than winter. The frequency of haemorrhagic stroke during winter was significantly greater than summer.Medicine Today 2022 Vol.34(1): 22-26